PENGARUH BUDAYA ORGANISASI, KEPEMIMPINAN DAN MOTIVASI TERHADAP KOMITMEN ORGANISASI (Studi Pegawai Politeknik Ilmu Pelayaran (PIP) Semarang) - Romanda Annas Amrullah (Fakultas Ekonomika dan Bisnis, Universitas Stikubank, 2016)
Success and agency performance can be seen from the performance achieved by its employees, therefore, the agency demanded that the employee is able to display optimal performance. Increasing the performance of the employees needs to be done in order to be optimized to work out where the performance is determined by the organizational culture, leadership, motivation and organizational commitment. This study aims to determine how much influence organizational culture, leadership, motivation and organizational commitment on organizational commitment. To determine the influence of organizational commitment to employee performance The population in this study were all employees of Semarang Merchant Marine Polytechnic as many as 190 people. Samples taken a number of 74 employees and the technique used is proportional random sampling. Statistical analysis was conducted on the multiple linear regression and hypothesis testing. Based on the results of data analysis can be concluded; There is a positive and significant influence of organizational culture on organizational commitment, there is a positive and significant impact of leadership on organizational commitment, there is a positive and significant effect of motivation on organizational commitment, there is a positive and significant influence of organizational culture, leadership and motivation together to organizational commitment, Keywords: Organizational Culture, Leadership Motivation, Organizational Commitment, Employee Performance